2020
DOI: 10.21083/partnership.v15i2.6124
|View full text |Cite
|
Sign up to set email alerts
|

Web-scale Discovery Service Adoption in Canadian Academic Libraries

Abstract: This study presents an overview of web-scale discovery service adoption in Canadian academic libraries. Web-scale discovery services (WSDS) have been widely embraced in Canadian academic libraries. EBSCO Discovery Service (EDS) is the most adopted system for colleges and institutes while Primo Central from Ex Libris dominates the university market for web-scale discovery services. Bundling web-scale discovery services with library services platform (LSP) implementations are increasing in Canada. This study sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Vaughan (2011, pp. 6-7) In a study on Canadian adoption of web-scale discovery platforms, Wong (2020) found that bundling of ILS-WSDS was widely reported in the academic libraries with an uncertainty of their disruptive mergers and acquisitions by vendors. Roy et al (2018) demonstrated how resource discovery tool VuFind can be integrated with ILS and digital repositories to reinvent OPACs as well as in harvesting external sources, and in India, we found four institutions have taken up VuFind implementation (VuFind, 2021).…”
Section: Higher Education Institutes In Indiamentioning
confidence: 99%
“…Vaughan (2011, pp. 6-7) In a study on Canadian adoption of web-scale discovery platforms, Wong (2020) found that bundling of ILS-WSDS was widely reported in the academic libraries with an uncertainty of their disruptive mergers and acquisitions by vendors. Roy et al (2018) demonstrated how resource discovery tool VuFind can be integrated with ILS and digital repositories to reinvent OPACs as well as in harvesting external sources, and in India, we found four institutions have taken up VuFind implementation (VuFind, 2021).…”
Section: Higher Education Institutes In Indiamentioning
confidence: 99%